Swirling Flow and Wall Shear: Evaluating the BioMimics 3D Helical Centerline Stent for the Femoropopliteal Segment - Timothy M. Sullivan; Thomas Zeller; Masato Nakamura; Colin G. Caro; Michael Lichtenberg (International Journal of Vascular Medicine)
The BioMimics 3D self-expanding nitinol stent represents a strategy for femoropopliteal intervention that is alternative or complementary to deployment of drug-coated stents or balloons. Whereas conventional straight stents reduce arterial curvature and disturb blood flow, creating areas of low wall shear, where neointimal hyperplasia predominantly develops, the helical centerline geometry of the BioMimics 3D maintains or imparts arterial curvature, promotes laminar swirling blood flow, and elevates wall shear to protect against atherosclerosis and restenosis. In the multicenter randomized MIMICS trial, treatment of femoropopliteal disease with the BioMimics 3D (n=50) significantly improved 2-year primary patency (log-rank test p=0.05) versus a control straight stent (n=26), with no cases of clinically driven target lesion revascularization between 12 and 24 months (log-rank test p=0.03 versus controls). In geometric X-ray analysis, the BioMimics stent was significantly more effective in imparting a helical shape even when the arterial segment was moderately to severely calcified. Computational fluid dynamics analysis showed that average wall shear was significantly higher with the helical centerline stent (1.13±0.13 Pa versus 1.06±0.12 Pa, p=0.05). A 271-patient multicenter international MIMICS-2 trial and a 500-patient real-world MIMICS-3D registry are underway.